Pengujian Stop Kontak Pintar Menggunakan ESP 32 - Aris Sudaryanto; Andri Eka Wahyudianto; Aldi Rizaldi (UNIVERSITAS STEKOM, 2020)
AbstractAt present electricity consumption in Indonesia is very high, so the costs to be paid for electricityconsumption are also high. Like it or not, everyone must make electricity savings both in terms of lifestyleand in terms of electrical equipment. To support electricity consumption savings, the we took the initiativeto design this Smart Socket Using ESP 32. This socket consists of ESP 32 microcontroller and relays, ESP32 is used as the main system control, while the relay functions to connect or disconnect the electricitybased on control from ESP 32. ESP 32 also has a wifi feature so that this tool can be controlled remotelyduring connection with internet network. From the tests that have been done, the smart socket that hasbeen made can work with a success rate of 100%.Keywords: Electricity, Socket, ESP